Dealing with radiation risks in systemic cancer treatment: Perspectives of practitioners and patients in French hospitals - Solenn Thircuir; Héloïse Pillayre; Johannes Starkbaum; Erich Griessler (PLoS ONE, 2025)
Systemic radionuclide therapy (SRT) using substances such as 177Lu is an approach in cancer treatment that aims to destroy malign tissues by injecting radionuclides directly into patients’ bodies via the bloodstream. This treatment connects benefits of care with risks related to radioactivity. Our research conducted in French hospitals shows that managing risk is an integral part of SRT, spanning from implementation, hospitals’ protocols, specific management, hospital settings, and training, to the individual experiences of health professionals and patients who are both exposed to radioactivity. This article argues that understanding how risks are managed in SRT not only requires making them identifiable, quantifiable, and calculable through medical devices in the context of evidence-based medicine, but also necessitates fostering trust throughout the treatment. This article explores and provides insights into three intertwined dimensions of trust in risk management: epistemic, (inter)-organizational, and interpersonal.